INCREASING STUDENTS’ READING COMPREHENSION THROUGH THINK-PAIR-SHARE TECHNIQUE - Nur Oktaviani; Rofiqoh Rofiqoh (e-Journal of ELTS (English Language Teaching Society), 2021)
This study aims to find out whether or not the use of think-pair-share technique can increase reading comprehension of the eleventh grade students of SMA Negeri 1 Tinombo. This research used a pre-experimental research design. The research population was the eleventh grade students of SMA Negeri 1 Tinombo which consisted of 147 students. The sample was selected by using a purposive sampling technique. The number of the sample was 27 of class XI MIA 1. The data were collected through pre-test and post-test about reading. The result of this research showed the mean score of the pre-test of the students was 58.44 and the post-test was 85.11. Therefore, the t-counted value (12.59) is higher than the t-table value (1.795). It proves the hypothesis is accepted which means the Think-Pair-Share Technique can increase students’ Reading comprehension.